Impact of Property Rights Reform to Support China’s Rural-Urban Integration : Household-Level Evidence from the Chengdu National Experiment - Deininger, Klaus; Jin, Songqing; Liu, Shouying; Xia, Fang (World Bank, Washington, DC, 2015)
As part of a national experiment in 2008, Chengdu prefecture implemented ambitious property rights reforms, including complete registration of all land together with measures to ease transferability and eliminate migration restrictions. A triple difference approach using the Statistics Bureau’s regular household panel suggests that the reforms increased consumption and income, especially for less wealthy and less educated households, with estimated benefits well above the cost of implementation. Local labor supply increased, with the young shifting toward agriculture and the old toward off-farm employment. Agricultural yields, intensity of input use, and diversity of output also increased. Improving property rights in peri-urban China appears to have increased investment and diversification.